Koldioxidutsläpp vid sticklingsproduktion av pelargonium x hortorum i Kenya jämfört med Sverige - Högemark Hilliges, Linnea (2008)
Long transport of products is an environmental issue discussed to an increasing extent. The consumers are increasingly aware of how far our comestibles really have been transported. The increasing levels of environmental emissions are something that concerns people. The question is nevertheless delicate and many choose to ignore it. This is no longer an option. We must act today; otherwise the effects will be disastrous. Today transportations stand for a big part of the emissions of environmental pollutions, and the most discussed is carbon dioxide. As a response among the transport discussions, the interest for Swedish cultivated and near produced products increases. At the same time as the consumers wants Swedish products, most don't think of that the Swedish cultivated tomatoes wintertime might contribute more to the negative environmental effects then the imported ones from abroad. This paper discusses the differences of three different productions system of geranium cuttings, Pelargonium x hortorum. Through a simplified life cycle assessment, LCA, their carbon dioxide contribution is calculated; wherein the first one is cutting production system the mother plants are cultivated in Kenya. From there the cuttings are transported by truck and aircraft, through Germany, to Sweden and put in cold storage while waiting for plantation. This system is compared with two cuttings systems where the mother plants are greenhouse cultivated in Sweden. For these cuttings a comparison is done between greenhouse heating with oil and heating with biofuel. The result of this study shows that the production system that generates with most carbon dioxide is the system where cuttings are cultivated in Sweden and the greenhouses are heated with oil. The second highest value has the system where cuttings are cultivated in Sweden and the heating of greenhouses is done with biofuel. In this system the main carbon dioxide contribution comes from electricity for light. The cuttings cultivated in Kenya have the lowest contribution of carbon dioxide emissions. Therefore, from a carbon dioxide point of view, it is better to cultivation the mother plants in Kenya and transport the cuttings to Sweden by aircraft, than to grow mother plants in Sweden.